Implementation of Inclusive Learning Through Letter and Reading Recognition: A Case Study at SDN Wonokusumo IV/43 via YouTube - Faida Nur Faiza; Rahmadina Amalia Habib; Leora Salsabilla Prastyana Putri (Bahasa Indonesia Prima, 2025)
This study examines inclusive learning practices by introducing writing and reading activities using YouTube video media in inclusive classes at SDN Wonokusumo IV/43. utilizing YouTube video media in inclusive classrooms at SDN Wonokusumo IV/43 Surabaya. The approach used is descriptive qualitative with a focus on teaching methods, interactions between teachers and students, and the impact of learning on students with special needs. Learning impact on students with special needs (ABK). YouTube video media used in learning is designed interactively with a learning-through-play approach, combining visual and auditory elements. The learning-through-play approach combines visual and auditory elements. Results The results showed that using videos as learning media increased learning motivation, active participation, and understanding of the material, especially for students with disabilities. In addition, this approach helped create an inclusive and adaptive learning environment for students with diverse needs. Diverse student needs. This finding confirms educational technology's important role in supporting effective, enjoyable learning and embracing diversity.